SIFAT KIMIA SELAI BUAH NAGA, KOMPOSISI MIKROFLORA DAN PROFIL SCFA FESES RELAWAN - Nurhayati Nurhayati; Gama Kusuma; Maryanto - (Jurnal Teknologi dan Industri Pangan, 2015)
Dragon fruit contains oligosaccharides, Including prebiotic ingredients, that are namely raffinose, stachyose, and fructo-oligosaccharides. The heat treatment process like jam producing can affect the functional properties of a food material. The aim of the research wereto know the effect of jam processing on chemical properties, and their prebiotic properties. Evaluation of the prebiotic properties was conducted by in vivo method i.e. probiotic and enterobacteria population of volunteers faecal (microflora composition), prebiotic index (PI) value and Short Chain Fatty Acid (SCFA) profile. The result showed that the processing of dragon fruit into jams decreased water content, β-sianin and dissolved particles but increased the Insoluble Indigestible Fraction (IIF). The PI value of dragon fruit jam were 1.70 for white dragon jam and 1.18 for red dragon fruit. The jam processing decreased PI value up to 0.49 (red dragon fruit jam) and 0.54 (white dragon fruit jam). The fresh dragon fruit and the jam produced short chain fatty acid (SCFA) i.e. acetic and propionic acid. It can be concluded that prebiotic properties of white dragon fruit better than red dragon fruit.